Comunicación interna y su incidencia en los procesos administrativos de los funcionarios del gobierno autónomo descentralizado del cantón Alfredo Baquerizo moreno “Jujan”. - Ramos Vargas, Ronny Rolando (2021)
In this case study entitled "INTERNAL COMMUNICATION AND ITS IMPACT ON ADMINISTRATIVE PROCESSES", it seeks to show how important internal communication is in different organizations, whether they are public or private, we will focus on finding information about what What is necessary is the internal communication between the employees of the decentralized autonomous government of the canton Alfredo Baquerizo Moreno "Jujan" and we will choose to interview a group of them to find out what their opinion is about this. It will be investigated if the top managers or bosses are working so that in this organization there is adequate internal communication, because although it is known that where there is good communication, there will be a good performance of the employees and therefore better management in the administrative processes that will optimize the service provided to citizens, so that they are happy and satisfied, and in turn will make the prestige of the organization grow.